Documentation Bulletin No. 6 - Planning Commission (Planning Commission, 1970)
The Study of the high-yielding varieties programme was continued during Rabi 1967-68 and covered wheat, paddy and jowar crops. The study for wheat was carried out in 15 districts of six major wheat producing States with a sample of 441 participants and 192 non-participants. The study for paddy and jowar was conducted in 14 districts (ten for paddy and four for jowar) in 8 States. As in the case of Kharif the main aspects covered in the study included planning, programming, organisation of supplies and credit, extent of adoption of various recommended improved practices and inputs.
Programme Evaluation Organisation Planning Commission Government of India